How Can Reasoned Transparency Enhance Co-Creation in Health Care and Remedy the Pitfalls of Digitization in Doctor-Patient Relationships? - Vincent Mabillard; Nicolas Demartines; Gaëtan-Romain Joliat (Kerman University of Medical Sciences, 2022)
This article addresses transparency in the current era of digital co-creation between healthcare professionals and patients. The concept of reasoned transparency is presented as a potential tool to guide the development of digital co-creation that is rapidly growing. The aim was to reflect on how doctors can apply transparency in their daily practice, following the shift from paternalistic to more collaborative relationships. On the one hand, our contribution indicates ways to take advantage of the existing digital tools to improve efficiency and increase patient trust, including the latest trend of artificial intelligence. On the other hand, this article identifies pitfalls of digitization and proposes reasoned transparency as remedy for the challenges rose by artificial intelligence. As a result, this perspective article tackles the issue of maintaining trustful and high-quality relationships between doctors and patients, increasingly challenged by the dissemination of online information and the pressures on healthcare professionals' accountability towards patients and the general public.